Exploring the influence of live streaming on consumer purchase intention: A structural equation modeling approach in the Chinese E-commerce sector - Yang Gu; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (Acta Psychologica, 2024)
The e-commerce landscape is evolving rapidly, and businesses seek novel ways to enhance their competitive edge. In this context, understanding consumers' purchase intentions becomes crucial. Drawing from the Stimulus-Organism-Response (SOR) theory, we propose a conceptual framework investigating the factors influencing purchase intention in e-commerce live-streaming marketing. The research adopts Structural Equation Modeling (SEM), Confirmatory Factor Analysis (CFA), and hypothesis testing to evaluate the relationships. The findings revealed that the attributes of live streaming, including the live streamer, the product, and the field, as well as trust and impulsiveness, positively influence purchase intention. This study provides a novel perspective on live streaming e-commerce with evidence on how e-commerce live streaming drives purchase intentions, enriches the content of live streaming e-commerce literature, and explores the practical implications for marketing managers who are looking for marketing by live streaming.
Keywords: Consumer Retail Behavior Studies; Digital Marketing and Social Media; Technology Adoption and User Behaviour